Effects of wet cupping therapy on blood parameters and quality of life of obese individuals / Mohd Anwar Md Yassin - Md Yassin, Mohd Anwar (2019)
Cardiovascular diseases (CVDs) are leading health problems caused by several risk factors, which include obesity. Obesity is defined as abnormal or excessive fat accumulation that may impair health and is the fifth leading risk for global deaths. Wet cupping therapy (WCT) is a recognized Malay traditional medicine that was shown pre-clinically to be effective against CVD parameters. This study was conducted to determine effects ofWCT on blood parameters and quality of life (QoL) of obese male individuals at baseline, pre- and post-WCT sessions and to look for differences between venous and cupping bloods samples. Obese male participants aged 22 until 39 years old were recruited with informed consent to receive two WCT sessions. Blood was collected via venipuncture from all participants at baseline, pre-and post-WCT sessions. Wet cupping sessions were conducted on days 28th and 35th. Venous and cupping blood samples were collected and analyzed. Study participants answer questionnaires related to quality of life. There were significant increase in aspartate transaminase (p < 0.05) and significant decrease in total protein (p < 0.001) between baseline, pre- and post-WCT sessions. Hematological parameters remained unchanged after WCT. Metabolite pathways via log fold change analysis uncovered insignificant regulation between baseline - pre-cupping venous bloods (p > 0.05), significant down regulation between pre-cupping - post-cupping (p < 0.001), and significant metabolites up regulation in cupping as compared to venous blood ( p ~ 0.001), including linoleic acid (LA), sphingosine I-phosphate (SIP) and glycochenodeoxycholate (GCDC). Three cupping points of WCT were found to affect several blood parameters and metabolic pathways associated with CVD. This findings provide evidence that WCT may be utilized as adjuvant treatment management against CVDs and obesity.